Study on the enhancement effect and mechanism of heat-induced gel strength of duck egg white by emulsified lipids. (15th April 2022) - Li, Ruiling; Xue, Hui; Gao, Binghong; Liu, Huilan; Han, Tianfeng; Hu, Xiaobo; Tu, Yonggang; Zhao, Yan
Abstract: This study investigated the effects and mechanisms of different types (lard, butter, and sunflower oil) and levels (6.43, 13, and 26.29 mL/L) of emulsified lipids on the physicochemical properties of heat-induced duck egg white gels (EWG). At 26.29 mL/L addition, the hardness of sunflower oil−egg white composite gel (S-EWG) was 8.4 N, which was significantly lower than that 11.4 N of lard−egg white composite gel (L-EWG) and 10.3 N of butter−egg white composite gel (B-EWG) ( p  < 0.05). In addition, L-EWG and B-EWG had higher water holding capacity (WHC), and surface hydrophobicity, as well as a more compact microstructure and lower spin−spin relaxation time ( T 2 ) and free sulfhydryl content than S-EWG. As the lipid content increased, T 2 decreased, free sulfhydryl content (lipid-groups and NEM-groups) decreased, and surface hydrophobicity increased for all three composite gels. These results collectively indicated that compared with emulsified sunflower oil, the emulsified lard and butter promoted the exposure of hydrophobic regions, hydrophilic polar groups, and sulfhydryl groups within the EWG molecules, thereby enhancing the hydrophobic interactions and crosslinking via disulfide bond formation (between gel proteins, between interfacial film and gel proteins) within the gels. Therefore, L-EWG and B-EWG exhibited higher hardness and WHC than S-EWG. Highlights: Emulsified lipids can increase the hardness of egg white gels. Emulsified lipids act as a physical filler effect in egg white gel network. Emulsified lipids promote the exposure of reactive groups within egg white gel. Disulfide bonds are formed between the interfacial film and the proteins. Enhancing effect of lard and butter on gel hardness is better than sunflower oil.